2015
DOI: 10.1073/pnas.1423035112
|View full text |Cite
|
Sign up to set email alerts
|

The collaborative roots of corruption

Abstract: Cooperation is essential for completing tasks that individuals cannot accomplish alone. Whereas the benefits of cooperation are clear, little is known about its possible negative aspects. Introducing a novel sequential dyadic die-rolling paradigm, we show that collaborative settings provide fertile ground for the emergence of corruption. In the main experimental treatment the outcomes of the two players are perfectly aligned. Player A privately rolls a die, reports the result to player B, who then privately ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
303
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(339 citation statements)
references
References 36 publications
29
303
1
6
Order By: Relevance
“…When others revealed their acceptance of politician 2 in the previous election, voters were more likely to do the same and to accept such a politician, thus conforming to group behavior and choices. A similar effect has been observed in experiments studying corruption in collaborative settings, and that reveal how these increase rates of corruption (Weisel and Shalvi 2015). No statistical evidence is found that the norm encouraged the very few voters who were willing to accept corruption to refrain from it.…”
Section: Regression Resultssupporting
confidence: 64%
“…When others revealed their acceptance of politician 2 in the previous election, voters were more likely to do the same and to accept such a politician, thus conforming to group behavior and choices. A similar effect has been observed in experiments studying corruption in collaborative settings, and that reveal how these increase rates of corruption (Weisel and Shalvi 2015). No statistical evidence is found that the norm encouraged the very few voters who were willing to accept corruption to refrain from it.…”
Section: Regression Resultssupporting
confidence: 64%
“…Closely related to our study are those of: Conrads, Irlenbusch, Rilke, and Walkowitz (2014) who found that people lie more when the returns to lying must be shared with another; Alempaki, Doğan and Saccardo (2016) who found that senders in a sender-receiver game lie less when the receivers played fairly in a prior dictator game; Weisel and Shalvi (2015) who found that, in a sequential twoplayer game in which both must lie for each to secure a positive monetary payoff, when the first player lies, the second player reciprocates by also lying; and Kocher, Schudy, and Spantig (2016) who found that communication within a group increases dishonesty. However, none of these prior studies investigate simultaneous coordination involving immoral behavior or isolate the effect of having a potential accomplice from other pro-social motivations for lying, while at the same time eliminating all possible forms of communication, including signaling intent through choice of action.…”
Section: Introductionsupporting
confidence: 68%
“…Cases in which people act honestly, even when no one is watching, abound, as it has been pointed out by recent research in experimental economics and psychology. For example, when people are asked to report the outcome from a (privately rolled) dice, knowing that their payoff will be equal to the outcome reported (so that they have an incentive to lie), not everyone lies (Fischbacher & Föllmi-Heusi, 2013; Kajackaite and Gneezy, 2015;Weisel and Shalvi, 2015). Similarly, experimental studies have shown that some people act honestly even when being dishonest would be beneficial to all parties involved (Erat & Gneezy, 2012;Cappelen, Sørensen & Tungodded, 2013;Biziou-vanPol, Haenen, Novaro, Occhipinti-Liberman & Capraro, 2015).…”
Section: Introductionmentioning
confidence: 99%